Plant Ecology of the Namib Desert - Van Damme, Patrick (Afrika Focus, 1991)
The Namib desert is reportedly the oldest desert in the world. It consists of a number of very distinct ecosystems, six of which are dealt with in this text. Among them are the sand dune, the dry river bed and the domed inselbergs vegetation. The importance of fog water absorption for the Namib flora is discussed. Two important and noteworthy endemic plant species, i.e. Welwitschia mirabilis and Acanthosicyos horrida are treated extensively, because of their great interest for plant physiology and ethnobotany, resp. Special attention is given to the importance of the CAM photosynthetic system for Namib desert plant survival. Where possible the ethnobotanic importance of the species is discussed. KEY WORDS: Acanthosicyos horrida. desert flora, drought stress, ethnobotany, succulents, Welwitschia mirabilis